The contribution of open education for improving causes of death certification practices - Teixeira, António (2023)
As recently demonstrated during the COVID-19 pandemic, mortality data provide a better understanding of epidemiological trends and the impacts of health policies within a population. The accurate and timely way information on causes of death is recorded, coded and published is therefore critical. Most countries apply the recommendations issued by the World Health Organization, in the International Statistical Classification of Diseases and Related Health Problems, currently in its 11th revision, [ICD-11] (WHO, 2023). In the European Union, however, the quality of data on causes of death differs considerably between member states. Despite using an official online platform for registering death certificates since 2014 (Law 15/2012), which speeds up considerably the processing of statistical updates on death causes (DGS, 2013), Portugal records a relatively high proportion of deaths attributed to poor conditions or other codes unnecessary in public health analyses, the so-called ‘garbage codes’ (Fihel & Muszynska-Spielauer, 2021). This is mainly due to inappropriate certification practices by many medical doctors unaware of the fact. However, to retrain a wide community of practitioners scattered around the country in a speedy way represents a massive challenge for public health authorities. Due to the limited resources available, using traditional in presence learning formats does not seem sustainable.